The days of Afrekete - Solomon, Asali (Farrar, Straus and Giroux, 2021)
"Inspired by Mrs. Dalloway and Sula, The Days of Afrekete is a tender, surprising novel about two Philadelphia women at midlife who rediscover themselves-and perhaps each other"--